Synthesis and analysis of electronic circuits and systems - Tong, Yit Chow (2008)
The main objective of this research project was to characterize the semi conducting gas sensor behaviour by D.C. and A.C. measuring techniques for improving the drift behaviour, the sensitivity of gas detection and the selectivity of gas in a mixture.